“Resilient City”? The Double Face of the 2006 Mardi Gras Celebrations in New Orleans - Aurélie GODET (E-REA)
Six months after Hurricane Katrina devastated the Gulf Coast, the residents of New Orleans decided to follow the tradition and organize a scaled-down Mardi Gras despite the perception that the city was still inundated with water. This article first analyses the 2006 carnival parades as the expression of a desire for “normality” as well as an attempt to memorialize Katrina. It then moves on to a discussion of the extent to which such a narrative of resilience was in fact devised and promoted by city officials and public editors in order to address various concerns, such as the decline of the tourism industry, divisions over the way reconstruction should happen, or the unflattering portrayal of the Crescent City in national and international venues. Finally, it examines how the combination of conservatism and transgression that characterized Mardi Gras discourse in 2006 echoes past debates on the propriety of carnival, making post-Katrina celebrations less an exception to the rule than an illustration of the double face of New Orleans Mardi Gras and of the city itself.